Monitoring progress towards planetary health. (7th December 2017) - Maini, Rishma; Law, Ronald; Duque, Francisco; Balboa, Gloria; Noda, Hiroyuki; Nakamura, Sachiko; Murray, Virginia
Abstract : International agreements must include appropriate indicators, published regularly